MARÍA LUZDIVINA CUESTA TORRE (ed.), «El legado literario de Castilla y León desde la Edad Media al Romanticismo», Peter Lang, Berlín, 2023, 386 pp. - Soriano Ruiz, Teresa Sarahí (Lectura y signo, 2023)
Reseña